Models of blockage-induced selectivity. (20th April 2017) - Barré, C; Talbot, J
Abstract: We examine blockage-induced selectivity in a particulate stream flowing through a channel. Each component of the mixture is characterized by the transit time, τ, necessary to pass through the channel. The model is motivated by filtration and other processes involving blockage. The transit time distribution of exiting particles depends on the entering particle distribution, ψ ( τ ), the intensity, λ, of the entering stream, and the blocking rule. With the simple rule that a blockage occurs whenever two particles are present in the channel, the properties of the exiting stream are directly related to the Laplace transform of the entering distribution, ψ ( λ ) . For any entering distribution, the exiting stream is enriched in faster moving components. The selectivity of a species in a binary mixture can be mapped to a thermodynamic system, namely a hard rod mixture at a given pressure and temperature that can model the adsorption of gas mixtures in nanopores. We also examine an alternative rule according to which blocking only occurs if a faster moving particle catches up to a slower one in the channel. The selectivity is quantitatively different compared to the simple blocking rule. In a binary mixture the majority component in the entering stream is further enhanced in the exiting stream, independently of the transit times.